Growth performance, oxidative stress, and antioxidant capacity of newly weaned piglets fed dietary peroxidized lipids with vitamin E or phytogenic compounds in drinking water - Silva-Guillen, Ysenia (2020)
Objective: This study evaluated the use of vitamin E and phytogenic compounds in drinking water on growth performance, oxidative stress, and immune status of piglets fed peroxidized lipids. Materials and Methods: In a 35-d study, 21-d-old weaned piglets (n = 96; 6.10 +/- 0.64 kg of BW) were assigned within sex and BW blocks to 1 of 4 treatments, using 24 pens (4 pigs per pen; 6 replications per treatment). Diets contained either 6% soybean oil or 6% peroxidized soybean oil. Pigs fed peroxidized soybean oil received drinking water without (control) or with supplemental vitamin E (100 IU/L of RRR-alpha-tocopherol) or phytogenic compounds (60 mu L/L for wk 1 and 30 mu L/L for wk 2 to 5). Results and Discussion: Peroxidized soybean oil decreased (P < 0.001) final BW (18.2 vs. 21.6 kg) and ADG (346 vs. 441 g/d) and tended to decrease ADFI (P = 0.14; 542 vs. 617 g/d) and G:F (P = 0.07; 645 vs. 715 g/kg). Peroxidation decreased serum vitamin E concentrations (P = 0.03), which could be restored (P = 0.01) by vitamin E in the water, but not phytogenic compounds. Peroxidized soybean oil decreased serum 8-hydroxydeoxy-guanosine, increased serum protein carbonyl, and had no effects on serum malondialdehyde or cytokines. Implications and Applications: Peroxidized soybean oil reduced growth performance of weaned nursery pigs, which did not appear to be related to oxidative stress or immune status. The negative effects of peroxidized soybean oil on animal performance could not be improved by supplementation of vitamin E or phytogenic compounds in the drinking water.